A greenhouse gas abatement framework for investment in district heating. (1st February 2018) - Björnebo, Lars; Spatari, Sabrina; Gurian, Patrick L.
Graphical abstract: Highlights: Method developed for categorizing the cost-effectiveness of district heating. Biomass and natural gas district heating effectively mitigate GHG emissions. District heating is competitive with other energy-saving building strategies. Performance of natural gas is highest due to efficiency in electricity generation. Abstract: Biomass resources could be used in the Northeastern U.S. in centralized district heating networks supplied by combined heat and power (CHP) plants to reduce consumption of petroleum resources (fuel oil), generate renewable electricity, and cost-effectively reduce greenhouse gas (GHG) emissions when supplying buildings with space and water heating. Alternatively, the CHP plants could be powered by natural gas, which would reduce GHG emissions relative to conventional, individual heating solutions owing to the improved efficiency of cogeneration. To assess the potential for investment in these technologies, hourly heat load demand in residential and commercial buildings in all New England and New York state towns (populations > 5000) was estimated and used to optimize the energy efficiency of district heating networks using MODEST software. All of the 116 studied locations without access to natural gas distribution infrastructure showed negative carbon abatement costs, the majority between −250 and −38 per Mg CO2 equivalents (eq.), when biomass-fed district heating was implemented due to significantly reduced operational costs and life cycle GHG emissions. Similarly, almost all (465 out of 467) locations connected to the natural gas grid were found to have negative GHG abatement costs, ranging from −4500 to −400 per Mg CO2 eq., demonstrating strong economic feasibility for district heating. Natural has an economic advantage over biomass in district heating due to its combined cycle CHP plants being able to generate more electricity per heat unit compared to biomass CHP plants and its lower O&M costs. District heating in all locations could abate 2.6 billion Mg of CO2 eq. at an economic surplus over 30 ears of continuous operation. Using a framework that integrated spatial tools, optimization, LCA, and cost evaluation, this study uniquely identified promising locations in the U.S. where district heating could be both environmentally and economically beneficial. This framework can be applied to other global regions that have significant space heating needs, for CHP implementation, and as a tool for identifying alternative building energy investments, such as improved insulation or individual space heating solutions, which in some cases could yield higher GHG reductions per dollar.